"A Cult of Cookie Bakers": The Spiritual Qualities of Youth Social Justice Organization Free the Children. (September 2019) - Funnell-Kononuk, Emma; Mosurinjohn, Sharday
This article analyzes the growing youth social justice initiative Free the Children/ME to WE as a kind of "spiritual movement" by demonstrating how the discourses utilized by participants and authorities resemble both the discourse of self-spirituality, as found among actual millennials, and the discourse of youth spirituality found in the developmental sciences literature. Building on previous research in which we characterized this family of organizations as a "new secular spiritual movement, " (Mosurinjohn and Funnell-Kononuk, 2017). we situate the phenomenological experience of its distinctive "WE spirituality" in the landscape of contemporary Western spirituality. Following on arguments that the politics of self-spirituality are more social change-oriented than previously acknowledged, we illuminate the logics of a spiritual movement that develops the "me" of the individual self into a part of the "we" of an imagined global community, by making spirituality coextensive with social civic engagement.